Application of HPLC method for simultaneous estimation of rutin and myricetin from micro and nano powders of leaves of syzygium jambos (L.) Alston - PADMA S. SATHE; VIDYA V. DIGHE (International Journal of Pharma and Bio Sciences, 2017)
A simple RP-HPLC method has been used for simultaneous quantitative determination of two flavonoids viz. rutin and myricetin, from the micro and nano powders of leaves of Syzygium jambos (L.)Alston.Micro and nano powders of leaves of Syzygium jambos (L.)Alston. were prepared by using simple stepwise powdering method. Coarse grinding of the dried leaves of Syzygium jambos (L.)Alston.was done using ice jacketed domestic mixer. This powder was sieved through a BSS 85 mesh sieve and was designated as micro powder. Further fine grinding was done by jet milling, followed by ball milling. This powder was designated as nano powder. The amount of rutin and myricetin obtained using the acidified methanol extract of leaf nano powderof Syzygium jambos (L.)Alston. was found to be significantly higher ascompared to the amount of rutin and myricetin obtained using the acidified methanol extract of leaf micro powder of Syzygium jambos (L.)Alston.